MODEL PEMBERDAYAAN INDUSTRI KECIL DI PEDESAAN UNTUK MENGURANGI KEMISKINAN - Arbaiyah Prantiasih (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2011)
Abstract: Empowerment of small industries is one way to extricate poverty. The government roles are needed in giving motivation, stimulation, and facilities to the craftsmen. The goals ofthis writing are describing the efforts of small industries craftsmen in maximizing their potentials in order to increase the strength of capital, raw materials, production, and marketing; the craftsmen's enthusiasmin achieving the success of small industries in the rural area; the involvement ofthe government in the empowerment of small industries in the rural area; the obstacles faced by the craftsmen in achieving the success; and the efforts done by the craftsmen in overcoming the obstacles. The method being used in this writing is qualitative approach. The subjects of the study are craftsmen (the owners and the employees), social leaders, and the officers of industry service. The resultsshow that the process of craftsmen empowerment really depends on the degree of autonomy owned by each craftsman. The process of craftsmen empowerrnent cannot be done through force of the government policy.